Paternal Strain Effects on Growth and Body Shape in Hybrid Striped Bass (White Bass ♀ × Striped Bass ♂). (24th July 2020) - Kenter, Linas W.; Kovach, Adrienne I.; Wojtusik, Kristopher J.; Reading, Benjamin J.; Berlinsky, David L.
Abstract: The farming of hybrid Striped Bass (HSB; White Bass Morone chrysops ♀ × Striped Bass  Morone saxatilis ♂ ) has been an established aquaculture industry in the United States for decades, but high production costs associated with performance variability remain a significant problem. To investigate the paternal effects on hybrid performance, Striped Bass males from Virginia, South Carolina, Florida, Texas and a fifth‐generation domestic strain selected for growth were used as sires in a half‐sibling, hybrid growth study. Eggs from individual White Bass ( n  = 11) were divided equally and fertilized with the fresh sperm from different Striped Bass sires ( n  = 18) to produce 53 hybrid families. Resulting larvae were stocked communally into ponds, seined as fingerlings, and separated into large‐grade, small‐grade, or ungraded groups for grow out. Juvenile HSB representing the three size‐grades were stocked into replicated indoor recirculating systems and grown until they attained market size (680 g [1.5 lb]). An additional group of the large graded fish was grown in outdoor tanks at a separate facility to observe genotype × environment interactions. Fin clips were collected during final measurements for genotyping and parentage assignment. The results indicated that large, small, and ungraded hybrids required 12, 14, and 17 months, respectively, to attain market size indoors. Wild‐strain‐sired HSB displayed a lower range in final weights compared to domestic fish and grew larger in the ungraded treatment only. Florida‐strain‐sired fish were the largest and had the greatest condition factor ( K ), Virginia‐strain‐sired fish generally had the lowest K, and the other strains had intermediate K ‐values. No differences in final weight were found in the small or large graded fish from recirculating systems, but the domestic strain produced the largest HSB grown in outdoor tanks. These results demonstrated that HSB growth is influenced by sire strain, culture environment, and grading strategies.